2018
DOI: 10.4067/s0718-18762018000200102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Product Smartness on Satisfaction: Focused on the Perceived Characteristics of Smartphones

Abstract: This paper investigates consumers' perceptions toward smartness characteristics of smartphones to understand the influence of product smartness on consumer satisfaction. Recent developments in information technology are accelerating the pace of change in products, particularly the emergence of smart products. Despite these technological advances, however, there is a lack of understanding about consumers who buy and use smart products. In this empirical study, five smartness dimensions of autonomy, adaptability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
(73 reference statements)
1
14
0
Order By: Relevance
“…According to the study about NFC mobile payment in South Korea , smartness was a predictor for perceived usefulness. Lee and Shin (2018) investigated consumer perception of smartphone smartness using five smartness characteristics: autonomy, adaptability, reactivity, multi-functionality and the ability to cooperate. They found that adaptability and multi-functionality had significant influences on consumer satisfaction.…”
Section: Hypotheses and Research Modelmentioning
confidence: 99%
“…According to the study about NFC mobile payment in South Korea , smartness was a predictor for perceived usefulness. Lee and Shin (2018) investigated consumer perception of smartphone smartness using five smartness characteristics: autonomy, adaptability, reactivity, multi-functionality and the ability to cooperate. They found that adaptability and multi-functionality had significant influences on consumer satisfaction.…”
Section: Hypotheses and Research Modelmentioning
confidence: 99%
“…The effect of product intelligence (smartness) on user recognition, perception, or attitude has received increasingly attention. How satisfied users are with these intelligent/smart characteristics of modern appliances needs to be empirically examined (Lee & Shin, 2018;Lin et al, 2017;Rijsdijk & Hultink, 2009). This study established a theoretical model to explain how users perceive the usefulness of leisure-sports appliances mediating the effect of tourists' self-image on intention to use.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…For example, Shin (2015) used a Customer Satisfaction Index (CSI) to assess the satisfaction of Korean citizens with services delivered via smartphones. The author's results also show that “ customer satisfaction has a direct effect on the behavioral intentions of customers.” Another study conducted on services delivered via smartphones also found that the main determinants of customer satisfaction were adaptability and multi-functionality (Lee and Shin, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In general, perceived user-friendliness or ease-of-use of technological innovations offers the strongest explanation of the impacts of such technologies on users' satisfaction and behavioral intention to continue using such innovations (Davis, 1989). In the realm of service technologies, perceived ease-of-use is defined as the service user's belief that the service channel is a clear interface that can be used with very little effort to effectively access and accomplish the service task (Lee and Shin, 2018; Karahanna and Straub, 1999). In the case of SCS, using the channels requires a certain level of technical skills; but evidence in the literature seems to suggest that SCS users are generally reluctant to seek help from a third party to acquire the skills (Alnaqbi, 2017).…”
Section: Conceptual Model and Hypotheses Developmentmentioning
confidence: 99%